Comparison of Anterior Chamber Depth Measured by IOLMaster and A-Scan Ultrasonography - Rabbani, Shafaq; Akram, Amjad; Yaqub, Amer; Ashraf, Ammara; Khan, Fatima (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare anterior chamber depth measurements by ultrasound A-scan and IOLMaster, and evaluate interdevice agreement and interchangeability.Study Design: Cross-sectional study.Place and Duration of Study: Study was conducted on subjects attending preoperative cataract surgery clinic at Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Nov 2018 and Jan 2019.Methodology: Eighty subjects between 15 to 80 years of age were enrolled in the study. Biometric measurements of all subjects were carried out by a single investigator. The values obtained were compared using paired t-test, Pearson correlation and Bland-Altman analysis.Results: Sixty-two men and eighteen women were examined. Mean age was 61.3 ± 11.8 years. Mean anterior chamber depth was 3.25 ± 0.42 mm with A-scan and 3.25 ± 0.47 mm with IOLMaster. Mean difference was 0.007 ± 0.32 mm which was not statistically significant (p=0.852).The values were significantly correlated (r=0.749, p